Evaluation of the Efficacy of a New Commercially Available Inactivated Vaccine Against Ovine Enzootic Abortion - Montbrau, Carlos; Fontseca, Mireia; March, Ricard; Sitja, Marta; Benavides, Julio; Ortega, Nieves; Caro, María Rosa; Salinas, Jesús (Frontiers in Veterinary Science, 2020)
Ovine enzootic abortion (OEA), caused by Chlamydia abortus, is an economically important disease in many countries. Inactivated vaccines have been used for many years as they induce immunity in sheep, although outbreaks of abortions have been described in vaccinated flocks. In addition, there is a commercially available live attenuated vaccine that provides good protective results. Recently however, reports question the attenuation of this vaccine and associate it with the appearance of outbreaks of OEA in vaccinated flocks. In the present study, a recently commercialized inactivated vaccine (INMEVA®; Laboratorios Hipra S.A., Amer, Spain) has been evaluated using mouse and sheep experimental models. In the mouse models (non-pregnant and pregnant models), the efficacy of INMEVA vaccine has been compared to an unvaccinated control group and to an experimental inactivated vaccine considered as a positive protection control (UMU vaccine). In the non- pregnant model, the UMU vaccine was more effective than the INMEVA vaccine regarding body weight gain or the presence of C. abortus in the liver, but both vaccinated groups (UMU and INMEVA) had significantly lower C. abortus in the liver compared to the control group. In the pregnant model in terms of reproductive failures, pups per mouse or the presence of C. abortus in the liver or uterus, no significant differences were found between both vaccines, inducing protection compared to the control group. In the ovine pregnant model, where INMEVA vaccine was compared only to an unvaccinated group, the results indicate that this new commercial vaccine is safe and provides a suitable degree of protection against C. abortus challenge. A 75% reduction in reproductive disorders and 55% reduction in animals with C. abortus shedding at day of parturition/abortion, in relation to infected control group, were observed. In addition, the average amount of chlamydial shedding on the day of parturition/abortion, and over the next 21 days, was significantly lower in the vaccinated group compared to control animals. The results suggest that this vaccine is adequate for the control and prevention of OEA; however, future studies are necessary to elucidate the type of protective immune response that it induces.